Safety procedures for exercise testing in the scenario of COVID-19: a position statement of the Società Italiana Scienze Motorie e Sportive - Venturelli, M.; Cè, E.; Paneroni, M.; Guazzi, M.; Lippi, G.; Paoli, A.; Baldari, C.; Schena, F.; Esposito, F. (Sport Sciences for Health, 2020)
Recent data on coronavirus disease 2019 (COVID-19) pandemic showed that the virus is mostly conveyed by respiratory droplets that are produced at high intensity especially when an infected subject coughs or sneezes. Therefore, elevated volume ventilations, usually reached during physical efforts and exercise, are a potential source of contamination. On the other hand, the lockdown period which has lasted for nearly 2 months and is actually involving several countries worldwide, obliged a large part of human population to sedentary behaviors, drastically reducing their physical activity level, and reducing their cardiopulmonary fitness. Therefore, cardiopulmonary exercise testing could be beneficial, so that a safe and well-weighted return to pre-lockdown active lifestyle can be efficiently planned. However, specific guidelines on exercise testing safety procedures in the era of COVID-19 are unavailable so far. This article is aimed to provide an overview of safety procedures for exercise testing during and after COVID-19 worldwide pandemic.